2018
DOI: 10.1097/mpg.0000000000001717
|View full text |Cite
|
Sign up to set email alerts
|

Enteroaggregative Escherichia coli Subclinical Infection and Coinfections and Impaired Child Growth in the MAL‐ED Cohort Study

Abstract: These data emphasize the public health importance of subclinical EAEC infection in early infancy in association with other pathogens and the need for improved maternal and child care, hygiene, sanitation, and socioeconomic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 34 publications
5
33
0
Order By: Relevance
“…Although EAEC was not associated with diarrhoea in children within the 24-60-month age group in this study, it was the most commonly detected pathotype from children with wasting. This observation is consistent with the findings of the recent the MAL-ED study, which reported that EAEC infection is associated with growth i shortfall, irrespective of disease 41 .…”
Section: Discussionsupporting
confidence: 93%
“…Although EAEC was not associated with diarrhoea in children within the 24-60-month age group in this study, it was the most commonly detected pathotype from children with wasting. This observation is consistent with the findings of the recent the MAL-ED study, which reported that EAEC infection is associated with growth i shortfall, irrespective of disease 41 .…”
Section: Discussionsupporting
confidence: 93%
“…Although EAEC was not associated with diarrhoea in children within the 24-60-month age group in this study, it was the most commonly detected pathotype from children with wasting. This observation is consistent with the ndings of the recent the MAL-ED study, which reported that EAEC infection is associated with growth shortfall, irrespective of disease [32].…”
Section: Discussionsupporting
confidence: 93%
“…We found an association with hospital admission for severe pneumonia, but the occurrence of malaria was too rare to be included in our analyses separately. However, in a multicountry birth cohort in low/middle-income countries, while diarrhoea was not a risk factor for poor linear growth, but presence of higher enteropathogen load in non-diarrhoea stools was associated with poor length growth 32 33…”
Section: Discussionmentioning
confidence: 80%